PENGARUH MONETER TERHADAP PERTUMBUHAN EKONOMI - ‘A’isyah Luthfi Alifah; RR Retno Sugiharti (Transpublika Publisher, 2022)
The purpose of this study is to investigate the impact that monetary variables have on the expansion of the Indonesian economy. Inflation, money supply, and exchange rates are all examples of monetary variables that are examined in this study. This study makes use of time series data spanning from 1990 all the way up to 2020. The Autoregressive Distributed Lag approach (ARDL method) is the one that is utilized for the analysis. According to the findings of the research, the independent variables and the dependent variables exert an influence on each other over both the short and the long terms. While the variable of inflation has no influence on economic growth over the long run, the variables of exchange rate and money supply have a major negative effect on economic growth. Inflation does not affect economic growth. On the other hand, in the short term, the variable that is the money supply has a big and negative impact on the expansion of the economy.